Peran Lingkungan Sekolah dan Orang Tua dalam Penguatan Anti Korupsi pada Anak Usia Dini - Ismi Choyrunnisa; Siti Maulidah Nur Azizah; Hilyatul Karimah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Instilling anti-corruption values ​​from an early age is crucial for building honest, disciplined, and responsible character in children. This study aims to analyze the role of the school environment and parents in instilling anti-corruption values ​​in early childhood at RA Darul Arifin. This study used a descriptive qualitative approach, with the principal, teachers, and parents as subjects. Data were collected through in-depth interviews, observations of learning activities, and documentation studies. Data were then analyzed using interactive analysis techniques that included data reduction, data presentation, and conclusion drawing. The results indicate that schools play a key role in instilling the values ​​of honesty, discipline, and responsibility through habituation activities, teacher role models, play-based learning, and the integration of religious activities. Parents play a role in reinforcing these values ​​through role modeling at home, open communication, and monitoring children's behavior. The main challenge comes from the influence of excessive viewing and use of gadgets. The implications of this study suggest that instilling anti-corruption values ​​will be more effective if there is ongoing synergy between schools and families through consistent communication and collaboration.